(untitled) (Comparative & International Education Series, 2022)
In an increasingly competitive labor market, the popularity of internships as a way to foster career readiness among college students is a growing imperative within higher education. However, there exist barriers to internship participation among international students, due to a misalignment between students’ needs and the career services offered to them. This qualitative study involved in-depth interviews with fifteen international students to explore access to internship opportunities and outcomes of their internship participation at a U.S. higher education institution, drawing upon intersectionality in higher education to examine the interview data. Findings show that career services, visa regulations, and students’ internship opportunities influence their employability. The chapter concludes with policy recommendations that better serve international students’ career paths. How to cite in APA: Gopal, A. (2022). Enhancing employability: Internship opportunities and outcomes for international students. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 77-94). STAR Scholars. [order hardcopy ]